EXERCISE -INDUCED BRONCHOSPASM IN MALE ATHLETES AT KARACHI - Ahad, Abdul; Sandila, M. Perwaiz; Siddiqui, Nadeem Ahmed; Ahmed, Syed Tousif (Journal of Ayub Medical College Abbottabad, 2003)
Background: Exercise is one of the most common precipitant of acute asthma encountered in clinical practice. To determine frequency of Exercise-induced Bronchospasm (EIB) in male athletes, who had represented or were aspiring to represent at national and/or international level. Athletes of different departments and institutes, district, provincial and national squad who were residing, practicing and attending training camps at Karachi during November 2000 to January 2002 were included. Methods: It’s an observational study on the frequency of EIB in athletes. A 21-item structured and pre-tested questionnaire was given for personal, biological and environmental information and an acquaintance session was conducted with each athlete to explain the procedure. Six minutes of competitive field free running Peak expiratory flow (PEF) rate, pulse rate and oxygen saturation were measured at 5-min, 15-min and 30-min. A player was considered EIB positive based on a post exercise decrement in PEF rate ³ 15% at any defined point of time. Results: The mean age of participating athletes was 27+6 years. Out of the one hundred and seventy-nine (n=179) athletes who participated in the study, 13 (7%) were found to be EIB positive. Conclusion: Our findings indicate that a significant number of our athletes suffer from EIB. It is suggested that either the department or national sports body should take the responsibility of screening for EIB making it a part of their training sessions. Key Words: Exercise; Bronchospasm, Asthma, Athlete